Introspection from research trainnig and educational research - Clavijo Gallego, María Camila (Universidad Pedagógica y Tecnológica de Colombia, 2014)
In the preschool teacher degree of the Corporacion Autonoma Universitaria del Cauca, it is revealed a series of tensions caused by the research training process and its influence in qualifying for the degree –among them the difficulties on dealing with the educational research process related to the alma mater established norms, are highlighted. This paper addresses to such tensions from a perspective that respects, above all, the senses and the feelings of a group of ten female teacher trainees who tackle, criticize and propose –from interviews and open and enjoyable writings– the compilation of experiences that provide a series of possibilities that positively affect the research process and the contribution to the development, meaning and sense of being preschool teachers.